2021
DOI: 10.1186/s13578-021-00708-z
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanism of neutrophil extracellular traps in cancer biological behavior

Abstract: As the predominant host defense against pathogens, neutrophil extracellular traps (NETs) have attracted increasing attention due to their vital roles in infectious inflammation in the past few years. Interestingly, NETs also play important roles in noninfectious conditions, such as rheumatism and cancer. The process of NETs formation can be regulated and the form of cell death accompanied by the formation of NETs is regarded as “NETosis”. A large amount of evidence has confirmed that many stimuli can facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 143 publications
1
30
0
Order By: Relevance
“…NETs have also been involved in brain disorders, including stroke, traumatic brain injury, multiple sclerosis, and Alzheimer’s disease [ 34 , 35 ]. Studies have been investigating anti-NETs compounds to treat or prevent clinical inflammatory diseases [ 27 , 29 , 32 , 36 , 37 ]. However, NETs have never been investigated in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…NETs have also been involved in brain disorders, including stroke, traumatic brain injury, multiple sclerosis, and Alzheimer’s disease [ 34 , 35 ]. Studies have been investigating anti-NETs compounds to treat or prevent clinical inflammatory diseases [ 27 , 29 , 32 , 36 , 37 ]. However, NETs have never been investigated in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, hypercitrullination of histones is mediated by protein-arginine deiminase type 4 (PAD4), which is a nuclear enzyme that citrullinates arginine residues by converting the amine groups to ketones ( 12 ). PAD4 can also mediates chromatin decondensation, which is the defining feature of cellular rearrangement in the formation of the NET ( 13 ). This process is followed by actin cytoskeletal disassembly and extracellular release of decondensed DNA by exocytosis or during plasma membrane lysis (mediated by NE and the pore forming GASDERMIN D), depending on the type of NETosis ( 13 ).…”
Section: The Role Of Netosis As a Key Function Of Neutrophils In Inna...mentioning
confidence: 99%
“…PAD4 can also mediates chromatin decondensation, which is the defining feature of cellular rearrangement in the formation of the NET ( 13 ). This process is followed by actin cytoskeletal disassembly and extracellular release of decondensed DNA by exocytosis or during plasma membrane lysis (mediated by NE and the pore forming GASDERMIN D), depending on the type of NETosis ( 13 ).…”
Section: The Role Of Netosis As a Key Function Of Neutrophils In Inna...mentioning
confidence: 99%
“…Tumor metastasis is the main cause of cancer mortality, and neutrophils are involved in this process ( 139 ). Multiple studies reported that NETs trap circulating cancer cells and release proteases, which results in tumor metastasis and proliferation ( 35 , 140 ). Najmeh et al.…”
Section: Nets and Hepatocellular Carcinoma Recurrencementioning
confidence: 99%